Analysis of the influence of selected technological parameters on the magnitude of vibrations during material machining by milling - Olejárová, Štefánia (Journal of Production Engineering, 2022)
With the current development of technology, more and more emphasis is being placed on product quality. Therefore, it is important in machining to continuously take care to reduce the influence of undesirable factors that adversely affect the machining process itself. Vibrations are one of the basic factors influencing the quality of machining. This paper analyzes the issue of vibration during milling. By measuring selected vibration parameters on the spindle head of a universal tool milling machine, information on the process of vibration magnitude in the milling process was obtained using a multiparametric vibration sensor. During machining, the magnitudes of vibration velocity and acceleration are recorded at speed changes of 71 rpm, 90 rpm, and 140 rpm. The measured data are tabulated and displayed in graphical dependencies. They are used to obtain the information needed to develop a proposal for a solution to the mentioned issue, which is the main objective of this research.